Pengaruh Ukuran Perusahaan, Profitabilitas, dan Likuiditas terhadap Struktur Modal pada PT Krakatau Steel Tbk Periode 2017-2024 - Renanda Dikfa Aristiani; Karari Budi Prasasti; Indah Yuni Astuti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the influence of firm size, profitability, and liquidity on the capital structure of PT Krakatau Steel Tbk during the 2017–2024 period. The independent variables in this study consist of firm size, measured by the natural logarithm of total assets (Ln Total Assets), profitability measured by Return on Equity (ROE), and liquidity measured by the Current Ratio (CR). The dependent variable is capital structure, proxied by the Debt to Equity Ratio (DER). A quantitative approach was employed, utilizing multiple linear regression analysis to test the hypotheses. The data used were secondary in nature, comprising quarterly financial statements of PT Krakatau Steel Tbk obtained from the Indonesia Stock Exchange (IDX) and other official sources. The empirical findings reveal that, partially, firm size has a negative and statistically significant effect on capital structure. This suggests that larger firms tend to rely less on debt financing. Profitability exerts a positive and significant influence on capital structure, indicating that more profitable companies are more likely to use debt to finance their operations. Conversely, liquidity exhibits a negative yet statistically insignificant impact on capital structure, implying that liquidity does not have a substantial effect on the company's capital structure decisions. Simultaneously, the three independent variables collectively have a significant effect on capital structure. The model’s coefficient of determination (R²) indicates that 26.7% of the variation in capital structure can be explained by the independent variables, while the remaining 73.3% is attributable to other factors not included in this study. These findings contribute to the understanding of financial decision-making within capital-intensive industries.